Innate lymphoid cells and infectious diseases - Ting Yuan; Qianhui Zhou; Yuqiu Tian; Yangjing Ou; YunZhu Long; YingZheng Tan (Innate Immunity, 2024)
Innate lymphoid cells (ILCs) are the main resident lymphocytes that mostly reside in tissues owing to the lack of adaptive antigen receptors. These cells are involved in early anti-infective immunity, antitumour immunity, regulation of tissue inflammation, and maintenance of homeostasis in the internal environment of tissues and have been referred to as the “first armies stationed in the human body”. ILCs are widely distributed in the lungs, colon, lymph nodes, oral mucosa and even embryonic tissues. Due to the advantage of their distribution location, they are often among the first cells to come into contact with pathogens.Relevant studies have demonstrated that ILCs play an early role in the defence against a variety of pathogenic microorganisms, including bacteria, viruses, fungi and helminths, before they intervene in the adaptive immune system. ILCs can initiate a rapid, nonspecific response against pathogens prior to the initiation of an adaptive immune response and can generate a protective immune response against specific pathogens, secreting different effectors to play a role.There is growing evidence that ILCs play an important role in host control of infectious diseases. In this paper, we summarize and discuss the current known infectious diseases in which ILCs are involved and ILC contribution to the defence against infectious diseases. Further insights into the mechanisms of ILCs action in different infectious diseases will be useful in facilitating the development of therapeutic strategies for early control of infections.